Teaching Design For Values Concepts, Tools & Practices - Rocco, Roberto; Thomas, Amy; Novas, María (TU Delft Open, 2022)
The process of identifying, interpreting, and implementing societal values in university education is an essential part of responsible innovation and designing for equitable, inclusive, and sustainable societies. While there is now a well-defined and growing body of research on the theory and application of designing for values (or 'value sensitive design'), at present the pedagogical dimension remains underexplored. Teaching Design for Values: A Companion is a resource for teachers of design-based disciplines who wish to foreground values more explicitly in their classes. With fourteen chapters written by both TU Delft educators and international contributors, the book aims to examine the concepts, methods and experiences of teaching design for values within a variety of fields, including urbanism, engineering, architecture, artificial intelligence and industrial design. Through its multi-disciplinarity, Teaching Design for Values proposes an expanded definition of 'design' to encompass a broad range of disciplines and processes that deal generally with 'future-imagining' and 'futurebuilding', including process management. In doing so it explores the ways that values may be expressed and analysed in a variety of different pedagogical contexts.